Transition-metal-catalyzed synthesis of quinazolines: A review - Tamatam, Rekha; Kim, Seok-Ho; Shin, Dongyun (Frontiers in Chemistry, 2023)
Quinazolines are a class of nitrogen-containing heterocyclic compounds with broad-spectrum 10 pharmacological activities. Transition-metal-catalyzed reactions have emerged as reliable and 11 indispensable tools for the synthesis of pharmaceuticals. These reactions provide new entries into 12 pharmaceutical ingredients of continuously increasing complexity, and catalysis with these metals has 13 streamlined the synthesis of several marketed drugs. The last few decades have witnessed a tremendous 14 outburst of transition-metal-catalyzed reactions for the construction of quinazoline scaffolds. In this 15 review, the progress achieved in the synthesis of quinazolines under transition metal-catalyzed 16 conditions are summarized and reports from 2010 to date are covered. This is presented along with the 17 mechanistic insights of each representative methodology. The advantages, limitations, and future 18 perspectives of synthesis of quinazolines through such reactions are also discussed.